Payments system study in the West African Monetary Zone (WAMZ) : strategy and policy framework. - West African Monetary Institute; Consultancy Associates Limited (Accra, Ghana : West African Monetary Institute, 2004)
The strategic objective of the report is to enable payments of any amount to be transferred among WAMZ member states quickly, efficiently, safely and reliably, so as to support, to facilitate and thereby to stimulate the trade in goods and services and free movement of capital within the zone.
"August 2004."
oif, 10/05/17
Loans
Keywords: Monetary unions; Payment system; Banks and banking; Africa, West